2000
DOI: 10.1021/ma0004312
|View full text |Cite
|
Sign up to set email alerts
|

n- and p-Doped Poly(3,4-ethylenedioxythiophene):  Two Electronically Conducting States of the Polymer

Abstract: Neutral poly(3,4-ethylenedioxythiophene) (PEDOT) thin films can be switched to an electronically conducting form either by oxidation (p-doping) or reduction (n-doping) in anhydrous organic solvents. The maximum attainable n-conductivity is ca. 1% of the maximum p-conductivity. However, based on spectroelectrochemical and in-situ conductance measurements, the p-conductivity regime can be divided into two domains, in which either positive polarons or bipolarons and free carriers are the major charge carriers. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
170
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(193 citation statements)
references
References 39 publications
20
170
1
Order By: Relevance
“…It can be concluded that well controlled n-type doping of the EDOT trimer is difficult to achieve, and the electrical properties of n-doped material are expected to be poor. This is in agreement with the results of previous studies of n-doped PEDOT, 25 which proved to have a much lower electrical conductivity than its p-doped counterpart, and was extremely unstable in air.…”
Section: Lithium Dopingsupporting
confidence: 93%
See 1 more Smart Citation
“…It can be concluded that well controlled n-type doping of the EDOT trimer is difficult to achieve, and the electrical properties of n-doped material are expected to be poor. This is in agreement with the results of previous studies of n-doped PEDOT, 25 which proved to have a much lower electrical conductivity than its p-doped counterpart, and was extremely unstable in air.…”
Section: Lithium Dopingsupporting
confidence: 93%
“…25 Nevertheless, n-doped PEDOT proved to be unstable even in a dry oxygen-free environment, and its maximum conductivity was about 1% of that of p-doped PEDOT. It is therefore interesting to study the electronic structure of both p-and n-doped EDOT trimer.…”
Section: Motivationmentioning
confidence: 99%
“…Some CP such as PEDOT (Ahonen et al 2000;Skompska et al 2005), polythiophene (Arbizzani et al 1995) or polyfluorenes (Ranger & Leclerc 1998) have an electronic affinity high enough to allow transitions from the neutral state to a reduced state, enabling them to store negative charges (by electron injection) on the chains at high cathodic potentials. In this case very stable solvents and salts are required, as electrolytes, to perform this reaction (3).…”
Section: N-dopingmentioning
confidence: 99%
“…A good example is poly(ethylene dioxythiophene) (PEDOT), a very well-known conducting polymer which, however, features very limited n-dopability. 29 One possible explanation of such behaviour is that silole-containing polymers fail to form extended electronic states, such as bipolarons, upon their reduction. Such behaviour was noted for PEDOT and is considered to be responsible for its low dopability and electronic conductivity in the cathodic potential range.…”
Section: Cyclic Voltammetrymentioning
confidence: 99%
“…Such behaviour was noted for PEDOT and is considered to be responsible for its low dopability and electronic conductivity in the cathodic potential range. 29 Electrochemical and chemiluminescence studies of a number of silole-containing molecules 14,30 suggest that reduction of the silole moiety may result in the formation of highly localized excited species with the negative charge centered on the silole. These excited states are also quite unreactive, as suggested by their long lifetimes.…”
Section: Cyclic Voltammetrymentioning
confidence: 99%